Some results of research and forecasting of groundwater salinization in the coastal zone of Soc Trang province - Nhan, Nguyen Thi; Trung, Dang Tran; Anh, Bui Thi Bao; Tung, Nguyen Xuan; Thanh, Nguyen Xuan (Vietnam Journal of Marine Science and Technology, 2019)
In recent years, the situation of salinity intrusion is very complicated and becomes more serious in the coastal area of Soc Trang province. In this research, SEAWAT modified water density flow model was used to forecast the salinity intrusion for Holocene aquifer (qh) and upper Pleistocene aquifer (qp3) according to the water use planning scenario. The results show that the impact of groundwater extraction process increases the TDS content in the aquifer, the salt water/fresh water areas change over time, the trend of salinity change increases. In Holocene aquifer, salt water area is relatively large and the TDS concentration increases towards the sea, however, fresh water area changes inconsiderably: In 2015 accounting for 17.42% and by 2030 accounting for 17.77% of aquifer area. In upper Pleistocene aquifer, the fresh water area declines significantly: In 2015 accounting for 9.35% and by 2030 only accounting for 7.53% of aquifer area.